Electronic transport properties of the first all-boron fullerene B40 and its metallofullerene Sr@B40. Issue 17 (12th April 2016) - An, Yipeng; Zhang, Mengjun; Wu, Dapeng; Fu, Zhaoming; Wang, Tianxing; Xia, Congxin
Abstract : The conductance of the first borospherene, B40, can be increased by embedding a strontium (Sr) atom in the cage. Abstract : The newly-discovered B40 is the first experimentally observed all-boron fullerene and has potential applications in molecular devices. Herein, we report the electronic transport properties of B40 and its metallofullerene, Sr@B40, using the first-principles technique. We obtain the conductance of B40 fullerene, which is about 130 μS and can be increased by embedding a strontium metal atom in the cage due to the decreased energy gap. Both the current – voltage ( I – V ) curves of B40 and Sr@B40 present perfect linear characteristics. Intuitively, it is assumed that the electron currents pass through the B40 fullerene mainly along the surface B–B bonds, while two types of new B–Sr–B bond currents and B→Sr→B hopping currents are presented for Sr@B40 due to Sr acting as a bridge. This study provides valuable information for the potential applications of future borospherene-based molecular devices.